The effects of family environment cognition and its difference perceived by adolescents and their parents on the treatment effect of non-suicidal self-injury behaviors in adolescents: a 1-year prospective cohort study - Li, Yalan; Li, Xin; Li, Yunge; Xiao, Yu; Li, Chunya; Chen, Jia; Li, Yao; Luo, Lishi; Su, Ding; Jia, Juan; Cheng, Haofei; Liu, Tianjiao; et al. (Frontiers in Psychiatry, 2023)
Introduction Family environment is the primary environment for adolescent growth and development, which is believed to have an important impact on the occurrence of non-suicidal self-injury (NSSI) behavior in adolescents. This study aimed to explore the effects of family environment cognition and cognitive differences perceived by adolescents and their parents on the treatment effects of NSSI in adolescents and to provide more potential perspectives for NSSI treatment. Methods A one-year prospective longitudinal sub-cohort investigation was carried out among 199 adolescents engaged in NSSI and one of their important guardians from the Longitudinal Psychosomatic Disease Study (LoPDS). The NSSI behaviors of adolescents were evaluated at 3 months, 6 months and 1 year after enrollment. The family environment scale (FES) and NSSI Behavior Questionnaire were used as assessment tools for family environment and adolescents NSSI behaviors. Multiple linear regression was used to investigate the role of family environment perception difference in the treatment effect of adolescent NSSI. Results After one year of follow-up, the perceived self-injury impulse score in recent 2 weeks, self-injury impulse frequency in recent 2 weeks, total number of self-injury in recent 2 weeks decreased significantly. The higher the adolescent family cohesion (Beta: 1.130, 95% CI: 0.886,1.373; p=0.032), parental family expressiveness (Beta: 0.818, 95% CI: 0.375,1.260; p=0.037) and parental family active-recreational orientation score (Beta: 0.609, 95% CI: 0.236,0.981; p=0.048), the better the treatment effect. However, higher adolescent family conflict (Beta: -0.838, 95% CI: -1.377,-0.298; p=0.024) were associated with lower treatment outcomes. The greater the cognitive difference between parents and adolescents in family cohesion (Beta: -1.307, 95% CI: -2.074,-0.539; p=0.014) and family conflict(Beta: -0.665, 95% CI: -0.919,-0.410; p=0.037), the worse the therapeutic effect of NSSI might be. Discussion There were certain differences in the cognition of family relationships between parents and adolescents, and subjective family relationship cognition and cognitive differences had a significant effect on the treatment effect of NSSI in adolescents. Helping them identify the cause of cognitive differences and conducting systematic family therapy from the points of difference may be another perspective to improve the treatment effect of NSSI in adolescents.